Histopathology of Duodenal Mucosal Lesions in Pediatric Patients with Inflammatory Bowel Disease: Statistical Analysis to Identify Distinctive Features. (November 2014) - Hardee, Steven; Alper, Arik; Pashankar, Dinesh S.; Morotti, Raffaella A.
Histopathologic lesions of the upper gastrointestinal tract (UGT) are common in inflammatory bowel disease (IBD) patients. Pediatric patients have a higher incidence of IBD-associated gastritis and duodenitis than do adults. This study aimed to identify histopathologic features of duodenal lesions in the pediatric population that are characteristic of IBD, compared to duodenal pathology of different etiopathogenesis. We performed a retrospective analysis of UGT biopsies from pediatric patients with a histopathologic diagnosis of duodenitis (0–18 years of age) over a 7-year period. We identified 40 cases of duodenitis associated with Crohn's disease (CD) and 10 cases associated with ulcerative colitis (UC) and compared the histopathologic characteristics of the duodenitis with age-matched controls consisting of 40 cases duodenitis associated with celiac disease and 40 non– Helicobacter pylori –associated (NOS) etiology duodenitis cases. The histologic features that were evaluated included presence of granulomas, duodenal cryptitis, erosion, lamina propria eosinophils, villous blunting, increased intraepithelial lymphocytes (IELs), and crypt hyperplasia, among others. Additionally, we evaluated the presence of associated gastritis in all of these groups. Statistical analysis to identify significant differences was performed using Kruskal-Wallis testing. Cryptitis was the most distinctive feature of IBD-associated duodenitis. Granulomas were exceptionally rare. The severity of villous blunting and presence of IELs was significantly different in the IBD versus the celiac group. There is a significant overlap with duodenal lesions of different etiopathogenesis, including villous blunting and eosinophilia. With the exclusion of granulomas, cryptitis seems the most distinctive feature of the duodenal lesions associated with IBD.